2015
DOI: 10.1002/ejlt.201400299
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity is a surrogate measure of the quality and stability of vegetable oils

Abstract: Total antioxidant capacity (TAC) may be a comprehensive oil quality index because of its potential association with chemical composition, oxidative stability, and fresh oil quality. We aimed to investigate the chemical determinants of the oxidative stability and TAC of oils using multivariate statistical analyses and the use of the TAC assay as a predictor of oil stability. Fatty acids, tocols, phenolic compounds, peroxide value, acid value, induction period (by the Rancimat test) and TAC (by the TEAC assay) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 37 publications
6
39
2
Order By: Relevance
“…Synergistic antioxidant activities have been reported between tocopherols and nitrogen-containing phospholipids such as phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine, all of which are present in tree nut oils and their minor component extracts and may help explain the high antioxidant activities observed for these products. Antioxidant capacity has been previously used as an indicator of the overall quality and oxidative stability of oils with good accuracy (Castelo-Branco et al, 2016). In the present paper we found similar trends in TBARS and antioxidants assays.…”
Section: Quality Characteristics During Storagesupporting
confidence: 85%
“…Synergistic antioxidant activities have been reported between tocopherols and nitrogen-containing phospholipids such as phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine, all of which are present in tree nut oils and their minor component extracts and may help explain the high antioxidant activities observed for these products. Antioxidant capacity has been previously used as an indicator of the overall quality and oxidative stability of oils with good accuracy (Castelo-Branco et al, 2016). In the present paper we found similar trends in TBARS and antioxidants assays.…”
Section: Quality Characteristics During Storagesupporting
confidence: 85%
“…This value was lower than those observed for cold pressed oils from almond (3.19), Brazil nut (1.11), hazelnut (1.29) and pecan (2.11) (Castelo-Branco et al, 2016). However, it was higher than the value calculated for açai oil (0.41), based on the composition reported by Rufino et al (2011).…”
Section: Oil Characterizationcontrasting
confidence: 61%
“…Compared to other vegetable oils extracted by cold pressing such as almond, Brazil nut, hazelnut and macadamia (Castelo-Branco et al, 2016), jussara oil showed higher oxidative stability, with longer induction periods. This can be related to the lower PUFA/SFA ratio in jussara oil as compared to the above-mentioned ones.…”
Section: Oil Characterizationmentioning
confidence: 83%
“…1 (1156.19 ± 16.32 mg/kg), while Yulin-6-21 had the lowest value (704.66 ± 2.53 mg/kg), which is still higher than that in rapeseed oil, a promising anti-aging oil (555-690 mg/kg) [30]. Moreover, the range of the total tocopherols in our study is much higher than that of extra virgin oleaster oil with a value ranging from 87 to 182 mg/ kg [15]; it is also higher than that in the refined oils of corn (11.05-15.27 mg/kg), soybean (15.81-18.45 mg/kg), sunflower (9.78-11.74 mg/kg) and canola (9.11-10.43 mg/ kg) [31]. Compared with the other common vegetable oils, BTBOs can be considered a good source of total tocopherols.…”
Section: Tocopherol Profilesmentioning
confidence: 78%